Educational Management Approaches in Islamic-Based Schools: A Systematic Literature Review - Nisrina Huwaida Qurrottu` Aini; Bambang Sumardjoko (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study discusses the educational management approaches applied in Islamic-based schools through a Systematic Literature Review. The urgency of this research stems from the need for madrasas, Islamic boarding schools, Islamic boarding schools, and integrated Islamic schools to strengthen governance, educational quality, student character building, and institutional competitiveness amidst social change, digitalization, and the demands of modern education. This study aims to identify educational management approaches commonly applied in Islamic-based schools, analyze their contribution to school governance and educational quality, and identify research gaps in Islamic educational management studies. The method used is a Systematic Literature Review with reference to the PRISMA 2020 guidelines. The selection process was carried out through an initial search of 159 articles, then filtered to 40 articles based on inclusion criteria, until 22 articles were obtained for in-depth analysis. The results of the study indicate that the educational management approach in Islamic-based schools is multidimensional and integrative. Dominant approaches include Islamic value-based leadership, kiai leadership, Qudwatuna leadership, academic kiai, Total Quality Management, strategic management, digital transformation, parental involvement, tahfidz program management, institutional branding, and educational service management. These approaches contribute to strengthening school governance through participation, transparency, accountability, administrative efficiency, ethical leadership, and institutional sustainability. Furthermore, these approaches improve educational quality through an integrated curriculum, teacher professionalism, religious character development, student achievement, digital services, and community engagement. This study concludes that educational management in Islamic-based schools needs to be developed through a more integrative, measurable, and contextual model so that it can be applied to various forms of Islamic educational institutions.